EFL Teachers’ Perceptions of Implementing Higher-Order Thinking Skills During English Online Learning - Mohammad Faisal Umam; Dyah Mukaromah; Sayit Abdul Karim; Erni Cahya Utami (RETORIKA: Jurnal Ilmu Bahasa, 2023)
This present study aims to explore the English as a Foreign Language (EFL) teachers’ perceptions of implementing the Higher Order Thinking Skills (HOTS) and their strategies in their English online learning and teaching during the COVID-19 outbreak. A qualitative descriptive design was applied for the present study. Five EFL teachers (1 male and 4 females) from SMKN 1 Seyegan, Yogyakarta were involved in the data gathering process. The data were obtained from a semi-structured interview conducted face to face, and the data were analyzed descriptively. The findings of the present study revealed that teachers' perceptions of implementing HOTS in English online learning and teaching during the COVID-19 outbreak were varied among them. Furthermore, three respondents: Mr. S, Mrs. ECU, and Mrs. IL found it hard to fully implement HOTS in their online learning and teaching due to several factors such as students' low level of English knowledge, the nature of the topic delivered, and digital literacy. The findings also revealed that there are four strategies applied by the EFL teachers in conducting HOTS during their English online learning, they are through the activities of 1) reading a text; 2) watching videos; 3) creating the learning products, and 4) stimulating questions.